A systematic review of nitric oxide donors and L-arginine in experimental stroke: effects on infarct size and cerebral blood flow - Willmot, Mark; Gray, Laura J.; Gibson, Claire L.; Murphy, Sean; Bath, Philip M.W. (Elsevier, 2005)
Background: Nitric oxide (NO) is a candidate treatment for acute ischaemic stroke, however published studies in experimental stroke have given conflicting results. Methods: We performed a systematic review of published controlled studies of L-arginine (the precursor for NO) and NO donors in experimental stroke. Data were analysed using the Cochrane Collaboration Review Manager software. Standardised mean difference (SMD) and 95% confidence intervals (95% CI) were calculated. Results: Altogether, 25 studies (s) were identified. L-arginine and NO donors reduced total cerebral infarct volume in permanent (SMD -1.21, 95% CI -1.69 to -0.73, p<0.01, s=10) and transient models of ischaemia (SMD -0.78, 95% CI -1.21 to -0.35, p<0.01, s=7). Drug administration increased cortical CBF in permanent (SMD +0.86, 95% CI 0.52 to 1.21, p<0.01, s=8) but not transient models (SMD +0.34, 95% CI -0.02 to 0.70, p=0.07, s=4). Conclusions: Administration of NO in experimental stroke reduces stroke lesion volume in permanent and transient models. This may be mediated, in part, by increased cerebral perfusion in permanent models. NO should now be tested in clinical trials in acute stroke.